Distance-resilient conductivity in p-doped polythiophenes - Röck, Eva Gabriela; Tsokkou, Demetra; Hunger, Basil; Horn, Maximilian M.; Zokaei, Sepideh; Kroon, Renee; Asatryan, Jesika; Martín, Jaime; Müller, Christian; Kemerink, Martijn; Banerji, Natalie (Materials Horizons, 2025)
Scalable organic electronic devices necessitate effective charge transport over long distances. We assess here the conductivity and its distance-resilience in doped polythiophene films with alkyl and oligoether side chains. We find that the polymers with oligoether side chains retain 80-90% of the conductivity over five orders of magnitude in distance (from tens of nanometers to millimeters), when doped with 2,3,5,6-tetrafluoro-tetracyanoquinodimethane (F4TCNQ). For P(g42T-T) co-processed with F4TCNQ, this leads to an over 100 times enhanced long-range conductivity (43 S cm−1) compared to doped poly(3-hexylthiophene) (P3HT, 0.2 S cm−1). Optimization of the oligoether side chain length and doping protocol pushes the conductivity to 330 S cm−1. Kinetic Monte Carlo simulations of nanoscale terahertz conductivity data reveal that the local mobility of the doped P(g42T-T):F4TCNQ film benefits from a higher dielectric constant (reduced Coulomb binding to the ionized dopant) and from lower energetic disorder. Those benefits persist on the macroscopic scale, while spatial charge confinement and a lack of connectivity hinder the long-range transport of moderately doped P3HT:F4TCNQ. However, strongly doping P3HT using magic blue leads to enhanced conductivity with distance-resilience >80%. The distance-resilience is generalized for different polymer:dopant systems once a highly conductive regime (>30 S cm−1) is reached. This highlights an effective strategy to overcome limitations in terms of electrostatic binding and multi-scale polymer ordering, enhancing both the short-range and the long-range conductivity of doped conjugated polymers.
Gesehen am 28.01.2026